20kV Cubicle Maintenance at PT PLN (Persero) APJ Banten Utara Rayon Prima Krakatau - Kautsar, Alif; Fatkhurrokhman, Mohammad (Fidelity : Jurnal Teknik Elektro, 2024)
The disturbances that often occur in 20kV cubicles are those with low insulation resistance values ​​caused by several factors such as environmental conditions, humidity levels, dust, temperature, water, pressure disturbances and other disturbances. If this disturbance is left unchecked, it can cause short circuits and electric current leaks. Another disturbance that is often experienced by 20kV cubicles is corona, where this disturbance causes a hissing sound in the cubicle and the appearance of rust on the indoor contact parts of the cubicle. If this condition occurs continuously it can cause serious damage to all 20kV cubicle components and cause losses for customers and PT. PLN (Persero). So to anticipate these problems, maintenance is required on 20kV cubicles. PT. PLN (Persero) carries out annual maintenance of 20kV cubicles to increase the insulation resistance value and overcome the problems of hissing and rust caused by corona events. This Industrial Practice assignment discusses the maintenance of 20kV cubicles in accordance with PT's SOP. PLN (Persero). After carrying out maintenance on the 20kV cubicle, the problems that occur can be resolved, such as increasing the insulation resistance value and the disappearance of the hissing sound and rust on the contacts of the 20kV cubicle.